ULCERATED INFANTILE HEMANGIOMA OF THE INTERGLUTEAL CLEFT TREATED WITH TOPICAL TIMOLOL - Fernandes, Sónia (2014)
Recent reports showed promising results with topical beta-blocker therapy for ulcerated infantile hemangiomas.The authors report the case of a 6-month-old preterm girl with an ulcerated infantile hemangioma of the intergluteal cleft successfully treated with topical timolol.